ESENSIALITAS PENEGAKAN HUKUM TINDAK PIDANA PENELANTARAN ANAK DALAM PERSPEKTIF BEST INTEREST OF THE CHILD - Firman Tri Wahyuono; Syukron Abdul Kadir; Edy Chrisjanto; Said Munawar (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the enforcement of the best interest of the child principle in child custody cases related to child neglect in the Indonesian legal system. This study uses normative legal research methods with approaches to legislation, conceptual, and comparative law, by analyzing national regulations and comparing child protection mechanisms in Sweden, Australia, and Canada. The results showed that the power of parents over children is not an absolute or invulnerable domain, but is limited by the obligation to protect the fundamental rights of children. the role of State parens patriae provides justification for state intervention in cases of child neglect through a system of mandatory reporting, Cross-Sector Coordination, as well as rehabilitative measures. However, law enforcement in Indonesia is still not effective due to weak institutional coordination, insufficient evidence, especially in cases of non-physical neglect, limited involvement of experts, and still strong cultural views that position child neglect as a private family affair. Hence the need for a systemic reform of the law, including the formulation of clearer indicators of child neglect, the strengthening of expertise-based evidence mechanisms, as well as the establishment of a victim-oriented rapid response system. Thus, state intervention is positioned as an essential legal and moral responsibility in protecting the rights of children, not as a form of violation of family privacy.